A Descriptive Study On Teaching Vocabulary Using Multimedia At The Seventh Grade Students Of SMP N 1 Tawangharjo Grobogan In 2012/2013 Academic Year - Saputro, Sulistyo Parmei; , Drs. Djoko Srijono, M. Hum; , Mauly Halwat, Ph. D. (2013)
This research paper aims at (1) describing the implementation teaching vocabulary using multimedia at the seventh grade students of SMP N 1 Tawangharjo Grobogan, (2) describing the problem faced of teaching vocabulary using multimedia at the seventh grade students of SMP N 1 Tawangharjo Grobogan, (3) knowing how the students respond the teaching vocabulary using multimedia at the seventh grade students of SMP N 1 Tawangharjo Grobogan. This is a descriptive qualitative research. The object of research is the process of teaching vocabulary using multimedia at SMP N 1 Tawangharjo Grobogan at the seventh grade students in 2012/2013 academy year. The methods of collecting data are observation, interview and document. The data are taken from the result of observation and interview after using multimedia in the teaching vocabulary. The result of this research shows that the implementation of teaching vocabulary using multimedia has a good result for the development in the students' vocabulary. The problems faced by the teacher in teaching writing are class management, difficulties in searching pictures related to the material, different capability of the students, and unstable motivation of the students. Based on the interview to the students, teaching vocabulary using multimedia get positive comments from students. They are not bored, but more enthusiastic to follow the teaching-learning process. The students look braver and more confident.